Die böhmischen Länder in den Wiener Zeitschriften und Almanachen des Vormärz (180-1848). Tschechische nationale Wiedergeburt - Kultur- und Landeskunde von Böhmen, Mähren und Schlesien - Kulturelle Beziehungen zu Wien. Teil III: Kunst - Marinelli-König, Gertraud (Verlag der Österreichischen Akademie der Wissenschaften, 2014)
Once more we are made aware of the fact that during the first half of the 19th century Bohemian musicians performed successfully outside their home country, in Europe as well as in the New World and in the Russian Empire, including careers in Vienna and we also learn that the readers of Viennese journals in the first place of the "Theaterzeitung" got firsthand information about the repertoire of the theatres in Prague and of theatres elsewhere. Reports and reviews about the life in the applied arts in the Bohemian lands being a rather lesser known chapter of art history allow us an insight in this field. The volume in question offers a reach source of information concerning the history of music, applied and performing arts in the Bohemian lands under Habsburg rule in the first half of the 19th century from the perspective of Viennese media.